To Overcome Oneself : The Jesuit Ethic and Spirit of Global Expansion, 1520-1767 - Molina, J. Michelle (Book collections on Project MUSE., 2013)
To Overcome Oneself offers a novel retelling of the emergence of the Western concept of "modern self," demonstrating how the struggle to forge a self was enmeshed in early modern Catholic missionary expansion. Examining the practices of Catholics in Europe and New Spain from the 1520s through the 1760s, the book treats Jesuit techniques of self-formation, namely spiritual exercises and confessional practices, and the relationships between spiritual directors and their subjects. Catholics on both sides of the Atlantic were folded into a dynamic that shaped new concepts of self and, in t